Have We Been Too Successful in Making Corporations Organism-Like? - Chakrabarti , Indranil; Chakrabarti , Sheila R. (M@n@gement, 2002)
This paper questions the persistent prescription, which has now also received a fillip from “new science”, for corporations to be more like organisms, especially in response to turbulence in the business environment such as exists in present times. We contend that another outcome of the prevailing turbulence, the trend towards the organizational career being outmoded, is particularly ironic because the organizational career, we argue, has been the organizing device that helped corporations become organism-like and more. It has done so in three significant ways: in developing the capacity to outlive their constituent individuals, just as multi-cellular organisms outlive their cells; in developing purposefulness—the capacity to choose and set goals of one’s own accord; and in developing even higher flexibility than organisms. Finally, alluding to misgivings about prospective organism-like physical artifacts, the paper suggests deeper studies on the social artifact, the corporation, as being already too organism-like.